Metabolomics and integrated network pharmacology analysis reveal Tricin as the active anti-cancer component of Weijing decoction by suppression of PRKCA and sphingolipid signaling. (September 2021) - Li, Jia-Xin; Li, Run-Ze; Sun, Ao; Zhou, Hua; Neher, Erwin; Yang, Jia-Shun; Huang, Ju-Min; Zhang, Yi-Zhong; Jiang, Ze-Bo; Liang, Tu-Liang; Ma, Lin-Rui; Wang, Jian; et al.
Abstract: Currently, conventional methods of treating non-small cell lung cancer (NSCLC) have many disadvantages. An alternative effective therapy with minimal adverse reactions is urgently needed. Weijing decoction (WJD), which is a classic ancient Chinese herbal prescription, has been used successfully to treat pulmonary system diseases containing lung cancer in the clinic. However, the key active component and target of Weijing decoction are still unexplored. Therefore, for the first time, our study aims to investigate the pharmacological treatment mechanism of Weijing decoction in treating NSCLC via an integrated model of network pharmacology, metabolomics and biological methods. Network pharmacology results conjectured that Tricin is a main bioactive component in this formula which targets PRKCA to suppress cancer cell growth. Metabolomics analysis demonstrated that sphingosine-1-phosphate, which is regulated by sphingosine kinase 1 and sphingosine kinase 2, is a differential metabolite in plasma between the WJD-treated group and the control group, participating in the sphingolipid signaling. In vitro experiments demonstrated that Tricin had vital effects on the proliferation, pro-apoptosis, migration and colony formation of Lewis lung carcinoma cells. Through a series of validation assays, Tricin inhibited the tumor growth mainly by suppressing PRKCA/SPHK/S1P signaling and antiapoptotic signaling. On the other hand, Weijing formula could inhibit the tumor growth and prolong the survival time. A high dosage of Tricin was much more potent in animal experiments. In conclusion, we confirmed that Weijing formula and its primary active compound Tricin are promising alternative treatments for NSCLC patients. Graphical Abstract: ga1 Highlights: Classic Weijing formula has been explored via network pharmacology and metabolomics for the first time. Weijing decoction is highly effective in suppressing lung cancer growth and prolonging survival. Tricin is the main active compound in Weijing decoction which has an inhibitory effect on protein kinase C alpha (PRKCA). Tricin reduces the expression of sphingosine kinase 1 and 2, resulting in regulation of the sphingolipid signaling. High-dose of Tricin suppresses lung cancer growth without reducing body weight in a xenograft mouse model.